On the preservation of the seed of the flax plant in Ireland - Malley, George Orme (Statistical and Social Inquiry Society of Ireland, 1869)
Although many treatises have been written, and many speeches delivered in this country within the last few years by landlords and agriculturists on the cultivation of flax, yet few have thought it worth their while to attract attention to the annual loss of the seed, which has been a continuous and deplorable instance of the reckless extravagance which characterizes the mode of cultivation hitherto universally adopted by the agricultural classes in Ireland. The value of flax seed imported from the Continent during the last three years into Ireland, has been in 1864, #205,929; 1865, #91,648; 1866, #146,700?Thom, page 772. If we could diminish sensibly this drain of capital, we would confer a great advantage on the country. The object of this paper is to show that such is within our power, and by ordinary exertion we can not only save one-half at least of this enormous annual expenditure, but also retrieve from utter and wanton waste a vast quantity of this valuable produce for feeding purposes.
Read, Tuesday, 18th February, 1868
Keywords: Irish agriculture; Flax seed; Flax cultivation; 314.15